Aktivitas Antioksidan Ekstrak Etanol 50% dan 70% Daun Kenikir (Cosmos Caudatus Kunth) Dengan Metode DPPH (2,2 Diphenyl-1 Picrylhydrazyl) - Astuti, Syafira Wiji; Sasmito, Ediati (Green Publisher Indonesia, 2024)
Antioxidants are molecules that work by warding off free radicals thereby reducing the damaging effects of free radicals. Coronary heart disease is a disease caused by free radicals. Kenikir leaves contain quite high flavonoid metabolite compounds, namely 12.197 mg QE/g. Flavonoids are among the largest natural phenolic compounds in plants that have bioactivity as medicines. The benefits of flavonoids are as anticancer, antifungal, anti-inflammatory, antimicrobial and antioxidant. The aim of this research was to determine the antioxidant activity of 50% and 70% ethanol extract of kenikir leaves (Cosmos caudatus Kunth.) using the DPPH method. This type of research is analytic cross sectional. The results of this study indicate that there is antioxidant activity of 50% and 70% ethanol extract of kenikir leaves (Cosmos caudatus Kunth.) using the DPPH method. The lowest IC50 value was 70% ethanol extract of kenikir leaves, namely 45.573 ± 0.241 ppm. The highest potential antioxidant activity is 70% ethanol extract of kenikir leaves with an IC50 value of 45.573 ± 0.241 ppm. The highest total flavonoid content was 70% ethanol extract of kenikir leaves, namely 17.209 ± 0.297%. The conclusion of this research is that 70% ethanol extract of kenikir leaves (Cosmos caudatus Kunth.) has the highest antioxidant activity with an IC50 value of 45.573 ± 0.241 ppm.